2018
DOI: 10.1159/000494837
|View full text |Cite
|
Sign up to set email alerts
|

A 2018 European Thyroid Association Survey on the Use of Selenium Supplementation in Graves’ Hyperthyroidism and Graves’ Orbitopathy

Abstract: Objective: Selenium (Se) supplementation has been suggested in the treatment of Graves’ disease (GD). We sought to investigate Se prescription patterns for GD across European countries. Methods: Members of the European Thyroid Association were invited to participate in an online survey investigating the use of Se in GD either without or with orbitopathy (GO). Of 872 invited members, 244 (28%) completed the survey. After exclusion of basic scientists and non-European members, 197 responses were retrieved out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
3
11
0
3
Order By: Relevance
“…In the light of the above, and in order to better characterize the diffusion of MIT procedures into current European clinical practice, the ETA conducted a survey among its members. The sample size was thought to be representative, and as previous surveys originated from the responses of approximately 40-50% of the clinically active members of the ETA [27]. Most important, nearly all the respondents declared a specific expertise in the management of thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…In the light of the above, and in order to better characterize the diffusion of MIT procedures into current European clinical practice, the ETA conducted a survey among its members. The sample size was thought to be representative, and as previous surveys originated from the responses of approximately 40-50% of the clinically active members of the ETA [27]. Most important, nearly all the respondents declared a specific expertise in the management of thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Whether selenium administration is of benefit in selenium-replete areas has to be confirmed. An European survey has shown that selenium supplementation is recommended by the majority of clinicians, both in patients with mild and moderate-to-severe GO (75), but there is no evidence of a beneficial adjuvant effect of selenium in patients with moderateto-severe and active GO.…”
Section: Management Of Mild Gomentioning
confidence: 99%
“…49% респондентов ответили, что назначают Se пациентам с заболеваниями ЩЖ редко (от случая к случаю), 21%часто/всегда, 21 %никогда. При ответе на вопрос о достаточной обоснованности такого рода терапии при АИТ, 41% респондентов ответил, что терапия является необоснованной, но тем не менее периодически они ее назначают своим пациентам, 20 % считают терапию обоснованной и назначают её всегда [14].…”
Section: обсуждение основного результата исследованияunclassified